Inter-Laboratory Validation of Method to Determine Residual Enrofloxacin in Chicken Meat - Joo Hee Chung; Kun Cho; Seongnyeon Kim; So Hyeon Jeon; Jeoung Hwa Shin; Jueun Lee; Yun Gyong Ahn (International Journal of Analytical Chemistry)
An inter-laboratory study was performed to evaluate the performance of a method developed for the quantification of enrofloxacin in chicken meat. Liquid-liquid extraction combined with a clean-up procedure based on solid-phase extraction followed by a liquid chromatography-tandem mass spectrometric method was used by three individual laboratories. All the investigated results of calibration curves and limits of quantification were within the acceptable range for regulatory testing of enrofloxacin. The three laboratories received blind a certified reference material to analyze in triplicate and assess using statistical analysis. From the results, no statistical differences were found between the laboratories in the precision of the method. Additionally, all the results of the z-score, which is an indication of fixed interval bias criteria for accuracy from the laboratories, fell within the allowable limits (±2σ). Based on this proficiency testing by inter-laboratory comparisons, the analytical method including the sample preparation step was proven to be applicable.